2016
DOI: 10.1021/acs.jcim.6b00615
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scaffold for Developing Specific or Broad-Spectrum Chitinase Inhibitors

Abstract: Chitinases play important roles in pathogen invasion, arthropod molting, plant defense, and human inflammation. Inhibition of the activity of a typical chitinase by small molecules is of significance in drug development and biological research. On the basis of a recent reported crystal structure of OfChtI, the insect chitinase derived from the pest Ostrinia furnacalis, we computationally identified 17 compounds from a library of over 4 million chemicals by two rounds virtual screening. Among these, three compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…The catalytic domains of OfChtI from O. furnacalis, human HsCht, and human AMCase were expressed in P. pastoris GS115 and purified as described previously (39,53,54). HsOGA was expressed in Escherichia coli and purified as described previously (40).…”
Section: Novel Targets Of Berberinementioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic domains of OfChtI from O. furnacalis, human HsCht, and human AMCase were expressed in P. pastoris GS115 and purified as described previously (39,53,54). HsOGA was expressed in Escherichia coli and purified as described previously (40).…”
Section: Novel Targets Of Berberinementioning
confidence: 99%
“…In the previous work, we noticed that compounds with a large conjugated plane were highly potent inhibitors of GH20 Hex (21,42) and GH18 chitinase (39). Berberine is a typical compound with a large conjugated plane.…”
mentioning
confidence: 96%
“…A hierarchical virtual screening strategy was used as described previously 13 , 27 , 29 . First, structural analogues to active hits were identified from a subset of commercially available compounds from ZINC database 30 employing substructure search and shape similarity calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The scarce nematode chitinase inhibitors may be, to a great extent, attributed to the lagged research on the structure of nematode chitinases. The availability of structure information could facilitate both structure-based virtual screening for inhibitor development and elucidation of inhibitory mechanism for inhibitor optimization [24][25][26][27] . Recently, we resolved the crystal structure of CeCht1 (PDB ID: 6LDU), a chitinase from the model nematode C. elegans 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we observed that compounds bearing a large conjugated plane were likely to be potent inhibitors of GH18 chitinase (27,30). In this study, exploiting our previously reported two constructs of OfChtII (OfChtII-C1, residues 1606 -1992; OfChtII-C2, residues 2056 -2438) (8), we screened the compound library of our lab which contains a mass of compounds with a large conjugated plane and obtained four potent inhibitors.…”
mentioning
confidence: 98%